Beyond immune checkpoint blockade: New approaches to targeting host–tumor interactions in prostate cancer: Report from the 2014 Coffey–Holden prostate cancer Academy meeting. Issue 4 (30th October 2014) - Miyahira, Andrea K.; Kissick, Haydn T.; Bishop, Jennifer L.; Takeda, David Y.; Barbieri, Christopher E.; Simons, Jonathan W.; Pienta, Kenneth J.; Soule, Howard R.
<x xml:space="preserve">Abstract</x> INTRODUCTION The 2014 Coffey–Holden Prostate Cancer Academy Meeting, held in La Jolla, CA from June 26 to 29, 2014, was themed: "Beyond Immune Checkpoint Blockade: New Approaches to Targeting Host–Tumor Interactions in Prostate Cancer." METHODS Sponsored by the Prostate Cancer Foundation (PCF), this annual, invitation‐only meeting is structured as an action‐tank, and brought together 72 investigators with diverse academic backgrounds to discuss the most relevant topics in the fields of prostate cancer immunotherapy and the tumor microenvironment. RESULTS The questions addressed at the meeting included: mechanisms underlying the successes and failures of prostate cancer immunotherapies, how to trigger an effective immune response against prostate cancer, the tumor microenvironment and its role in therapy resistance and tumor metastasis, clinically relevant prostate cancer mouse models, how host–tumor interactions affect current therapies and tumor phenotypes, application of principles of precision medicine to prostate cancer immunotherapy, optimizing immunotherapy clinical trial design, and complex multi‐system interactions that affect prostate cancer and immune responses including the effects of obesity and the potential role of the host microbiome. DISCUSSION This article highlights the most significant recent progress and unmet needs that were discussed at the meeting toward the goal of speeding the development of optimal immunotherapies for the treatment of prostate cancer. Prostate 75:337–347, 2015. © 2014 Wiley Periodicals, Inc.